AN ANALYSIS OF MORAL VALUE IN “THE MAZE RUNNER” A FILM BY WES BALL 2014 - Dewi Qomaria; Suyadi Suyadi; Erisa Kurniati (JELT: Journal of English Language Teaching, 2018)
The aim of this research is to analyze the moral value in “The Maze Runner” film, the researcher limited the problem into the analysis the moral value in “The Maze Runner” film. In this research, researcher used descriptive qualitative research. The object of this research is a film by Wes Ball “The Maze Runner”. In this research, there are fourteen data found in relation to moral values in “The Maze Runner” film.Keywords: Analysis, Moral Value, Film.